Carte Physique et Politique de lâ€™AmeÌrique Septentrionale - Dussieux, L. (Louis), 1815-1894 (Dussieux, 1856)
This map shows North and Central America and the surrounding areas. Regions are outlined in color based on the controlling nations explained by a key in the lower left corner. Major cities, bodies of water, and geographic features are noted (with relief shown by hachures). Prime meridian: Paris.